Oil Prices, Economic Growth and Emigration: An Empirical Study of Transmission Channel - Burakov, Dmitry (International Journal of Energy Economics and Policy, 2017)
In this paper, we set ourselves a task to test a hypothesis of transmission channel of oil shocks to migration decisions of the population. According to the hypothesis, oil prices' shocks have a direct impact on economic growth (assuming the economy's dependence on oil export's revenues) and indirectly affect migration trends according to a classical migration theory in Heckscher-Ohlin paradigm. The hypothesis is tested on the example of Russia for the period from 1990 to 2015. To detect long-term relationship between sampled variables we use VECM models; for testing presence of short-run dependencies, we use Wald test. Structural and dynamic responses to shocks in short run are tested by variance decomposition and impulse response functions. In result, we are able to confirm the hypothesis. On the one hand, existence of a long-term relationship between oil prices, economic growth and emigration is established. In the short-run, we find direct causality between oil prices and economic growth, as well as between economic growth and emigration. Thereby, existence of transmission in form of indirect channel of oil prices' shocks on migration decisions of households is confirmed. Keywords: world oil prices, economic growth, migration, transmission channel, acceleration JEL Classifications: F22; O1; O47; Q41, Q43